Analisis Model Kolaborasi Entitas Bisnis Dan Pesantren Dalam Pengelolaan Unit Usaha - Muhammad Habib Ali Ramadhan Irvan; Ade Nur Rohim (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Economic development around the Darul Quran Mulia Islamic Boarding School is growing rapidly, but as an educational institution, of course, it should not only focus on education, but must also focus on economic management from the business perspective. This study aims to examine the roles and efforts that can be carried out by the Darul Quran Mulia Islamic Boarding School in managing the business units it owns. This research is a field research with a descriptive qualitative approach. The primary data sources in this study were PT. Berkah Group and employees of the Darul Quran Mulia foundation. Secondary data sources are documentation of the Darul Quran Mulia Islamic Boarding School and books and journals that discuss the economics of Islamic boarding schools. The analytical method uses interviews and documentation with qualitative descriptive data analysis techniques using inductive thinking patterns. The results of this study indicate that the Darul Quran Mulia Islamic boarding school operates a collaboration model with PT. Berkah Group in managing business units, in this case the Darul Quran Mulia Islamic boarding school acts as a customer while PT. Berkah Group serves as a service provider